System and apparatus for upgrading concentrated executable computer software code without reconcentration - CHEN DONGNI; PISUPATI RAVIKUMAR (2006)
In upgrading a concentrated executable computer code with an upgrade code, a first indexed list is created of a plurality of index references corresponding to first identifiers of the first type code structures in the concentrated code, the first indexed list further containing upgrade flags to indicate whether corresponding first type code structures identified by the first identifiers have been upgraded. A first indexed upgrade list is created of a plurality of index references corresponding to first identifiers of the first type code structures in the upgrade code. A state of each upgrade flag is set to indicate whether a corresponding first identifier in the first indexed list has been upgraded based on comparing the first identifiers in the first indexed upgrade list with the first identifiers in the first indexed list.